DETEKSI DINI DAN SKRINING ANEMIA PADA REMAJA PUTRI DI SMK NEGERI 5 MUARO JAMBI - Tri Wahyuni; Asmeriyani Asmeriyani; Anipah Anipah (Jurnal Pengabdian Masyarakat, 2026)
Anemia is one of the major public health problems frequently experienced by adolescent girls in Indonesia. This condition may occur due to an increased need for iron during adolescence, blood loss during menstruation, and a lack of knowledge about anemia and its prevention. According to data from the Kementerian Kesehatan Republik Indonesia (2018), the prevalence of anemia among individuals aged 15–24 years reaches 32%. Anemia during adolescence has the potential to persist into pregnancy and increase the risk of obstetric complications. The aim of this community service activity was to conduct early detection of anemia through screening and to improve adolescent girls’ knowledge regarding anemia prevention. The implementation method consisted of several stages: (1) site survey and coordination with the school; (2) anemia screening through clinical sign assessments and hemoglobin level measurements using the Sahli method; (3) health education on anemia and iron supplementation through iron tablets; and (4) evaluation of the activity outcomes. This program was participated in by 54 female students from grades X and XI at SMK Negeri 5 Muaro Jambi. The screening results showed that 38 students (70.3%) experienced clinical symptoms of anemia, such as dizziness upon postural changes, fatigue, and low blood pressure. Two students (3.7%) were found to have hemoglobin levels below 12 g/dL, indicating mild anemia. These findings highlight the importance of early anemia screening and health education as preventive measures among adolescents. In conclusion, anemia screening and health education can help detect mild anemia cases and increase awareness among adolescents of the importance of iron intake and iron supplementation. Continuous collaboration between schools and healthcare workers is essential to ensure routine anemia screening and nutritional education. Keywords: anemia, adolescent girls, screening, health education, hemoglobin